Soymilk protein detection in milk- A review - Gautam, Priyae Brath; Sharma, Rajan; Ranvir, Suvartan; Gandhi, Kamal; Mann, Bimlesh (Indian Journal of Dairy Science, 2019)
Milk being considered as a complete food can also be easily adulterated by a large number of adulterants. Such type of adulteration deteriorates its quality and can affect the health of the consumers. Processing such type of adulterated milk can affect certain processing parameters in the dairy industry. A large number of adulterants have been used worldwide and have been reported like water, urea, carbohydrates, foreign proteins, vegetable or animal fats, melamine and so on. Unscrupulous producers even add hazardous substances to gain profits. This review focuses on the detection of soy proteins by different methods like RP-HPLC, UHPLC, SDS-CE, SDS-PAGE, SDS-PAGE/MS, FPLC, NIR spectroscopy, FTIR, Lateral flow assay, Biosensors, LC/MS-MS that have been developed and used from the last 25 years. From long and time-consuming electrophoretic to biosensor-based methods, this review will provide a clear understanding of the various assays.